Pandan Tea (Pandanus amaryllifolius Roxb) as Lowering Blood Sugar Levels in Type 2 Diabetes Mellitus - Faza Saiqur Rahmah; Chella Sonia; Vanda Rizky Rohmatulloh; Nisrina Shabry Habibie; Muhammad Rizal Novianto (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
Type 2 diabetes mellitus is a non-communicable disease caused by metabolic disorders characterized by increased blood sugar levels caused by decreased insulin secretion or insulin resistance. This research aims to make a product from pandan leaf tea that can be consumed as well as to find out whether pandan leaf tea has alkaloid, flavonoid, saponins, tannins, and polyphenols content that could lower blood sugar level. This research uses a descriptive method by collecting data based on journals and references and qualitative method by conducting organoleptic, hedonic, and phytochemistry tests. As a result, more than 50% of the respondents like the color and smell of the product very much, and more than 50% of the respondents like the taste of the product. 35 out of 68 respondents rate the product with a score 4 out of 5. And for the result of phytochemistry tests, researchers found that pandan leaf tea contains all chemical components described in research objectives. It concludes that FANDANCO Tea contains chemical compounds as described. Also, it got positive responses from the community.